Morphological characterization of Indian pummelo (Citrus maxima) - DUBEY, A K; SHARMA, R M; AWASTHI, O P; SHARMA, NIMISHA; KHOLIA, ANJANA (The Indian Journal of Agricultural Sciences, 2019)
The present study was conducted with the aim to characterize different indigenous pummelo genotypes based on 19 quantitative and 9 qualitative traits. Leaf shape, leaf margin shape, leaf apex shape, petiole wing, petiole wing shape, fruit shape, fruit apex shape, fruit axis, fruit surface texture and pulp colour were the main qualitative characters of study. The higher coefficients of variation were determined for petiole area (36.33%), juice quantity (17.38%), leaf area (14.50%) and fruit weight (14.22%). Principal component analysis (PCA) for quantitative traits indicated that six PCA had Eigen-value greater than one. The cumulative variation explained by six components, viz. leaf length, fruit width, leaf length: width ratio, leaf area, petiole area and lamina wing ratio accounted over 86.12 % variability. However, the result of the PCA for qualitative traits showed that three parameters namely leaf shape, leaf margin shape and leaf apex shape among 10 Principal Component Axis (PCA) had Eigen-values greater than one, and accounted for over 70.23% of the total variability. Based on PCA and coefficient of variation, traits like fruit weight, seed content, juice content, leaf and petiole area, leaf length, leaf width and leaf length: width ratio had significant involvement in pummelo diversity, and can be used in differentiating accessions of citrus.